Evaluation of the Accusport® lactate analyser - Bishop, D. (International Journal of Sports Medicine, 2001)
It has been suggested that lactate concentrations may provide a guide to an optimal training intensity. However, lactate concentrations established during incremental exercise in the laboratory are not always indicative of what is occurring during constant-load exercise at the same intensity. Ideally, lactate concentrations should be measured during a training session and immediately reported to the athlete to ensure that the athlete is working at the desired intensity. The purpose of this investigation was, therefore, to determine the reliability and validity of a compact, portable lactate analyser (ACCUSPORT; Boeringer Mannheim, Castle Hill, Australia). A total of 224 capillary blood samples were taken from athletes who took part in routine laboratory testing. Seventy-three of these capillary blood samples were analysed in duplicate with the Accusport for determination of intraclass, single-trial reliability. Day-to-day intraclass reliability of the Accusport was assessed by analyzing known concentrations of aqueous lactate solutions on seven consecutive days. The validity of the Accusport analyser was assessed by comparing the 224 capillary blood lactate concentrations determined on the Accusport with the lactate concentration obtained using a MICRO STAT LM3 (Analox Instruments Ltd., London, UK). In addition, lactate parameters derived from the lactate concentrations obtained with the two analysers were compared. The Accusport showed high single-trial intraclass reliability (R = 0.992; Standard Error of Measurement [SE(M)] = 0.3 mmol x l(-1); n = 73) and high day-to-day intraclass reliability (R = 0.993; SE(M) = 0.4 mmol x l(-1); n = 42). Despite a strong correlation between blood lactate concentrations obtained on the two analysers (r = 0.96; n = 224) the limits of agreement were + 1.9 to - 2.2 mmol x l(-1). Although the mean values for power output, HR and lactate concentration associated with the lactate parameters were not significantly different when determined on the Accusport or Micro Stat, some individuals did record large differences between analysis methods. In summary, the results of this investigation have shown that lactate concentrations can be reliably determined within a single trial and from day-to-day using the Accusport analyser. However, for some athletes, it is not valid to compare lactate concentrations or lactate parameters determined on the Accusport with those determined using the Micro Stat LM3 lactate analyser.